Literacy Transformation: Implementation of Digital Library at Tebuireng Islamic Boarding School Jombang - Junaidi, Erik; Laksana, Inggil (Proceeding International Conference on Religion, Science and Education, 2025)
This study examines the process of literacy transforma&on through the implementa&on of digital libraries at Tebuireng Islamic Boarding School, Jombang. In the digital era, the role of libraries in suppor&ng informa&on literacy has undergone significant changes. This study aims to analyze the implementa&on of digital libraries in tradi&onal Islamic boarding schools and their impact on the literacy culture of students. The research methodology uses a qualita&ve approach with a case study method. Data were collected through in-depth interviews, par&cipant observa&on, and document analysis. The results of the study show that the implementa&on of digital libraries has brought posi&ve changes in the pasern of informa&on access and literacy culture of students. Key findings include increased interest in reading, expanded access to sources of knowledge, and integra&on of technology in learning yellow books. Challenges include resistance to change, limited technological infrastructure, and the need for digital training. Strategies to address these challenges include gradual socializa&on, infrastructure development coopera&on, and digital literacy training programs. The study concluded that literacy transforma&on through digital libraries in Islamic boarding schools is a strategic step in preparing students to face the informa&on era. The proposed recommenda&ons include the development of digital content based on local wisdom of Islamic boarding schools, increasing collabora&on between Islamic boarding schools in sharing digital resources, and further integra&on between tradi&onal learning methods and digital technology.